PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS SURAT PRIBADI - April Wijanarko (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The study design using the design of classroom action research ( CAR ), with two cycles. Methods and techniques of data analysis used is descriptive method descriptive qualitative and quantitative, using data collection techniques are engineering test and nontes. The results showed an increase in product value averaged 68.2 on prasiklus, in the first cycle an average of 72.2 after the second cycle of the average value of 88.5 with an increase in the percentage of completeness 30% on the value of the product prasiklus, then on I cycle 35%, and the second cycle of 100% completeness of product value. In terms of the results of evaluation carried out in two cycles showed an increase of the average value of 62 on prasiklus, the first cycleincreased to an average of 69, and the second cycle value increased to an average of 94.5 with a percentage of completeness of test scores 15% on prasiklus,the first cycle increased to 40%, and the second cycle to 100%, with an average value of the end of writing a personal letter reached 91.5.